Personal Vocabulary Notes (PVN) Method Affects The Students’ Vocabulary Mastery at IAIN Parepare - Hasanah, Nurul; Mada Ali, Syahban (Jurnal Ilmiah Multidisiplin Amsir, 2022)
The purpose of this study was to analyze the effect of the Personal Vocabulary Note (PVN) method on the vocabulary skills (Noun and Adjective) of the second semester students of the English Education Study Program IAIN Parepare. This study uses the Class Action Research method in which each cycle contains three teaching processes. The object of this research is the second semester English Education Students of IAIN Parepare with a total of 30 students. The research procedure that has been carried out is to apply 2 research cycles consisting of four stages; they were: planning, action, observation and reflection. The first step is carried out by giving a diagnostic test to students. After that given 2 cycles consisting of 3 meetings each cycle by applying the PVN method. The research instruments used were observation sheets and vocabulary tests. After the data was collected, it was analyzed using descriptive statistical analysis method. The results of this study indicate that the use of PVN in learning has a positive effect on students. The results found that the students' vocabulary rose from the diagnostic test until 2 cycles were run. The data shows that in, the student's diagnostic test was 64, rose in the first cycle, which was 72.77, and skyrocketed in the second cycle with a mean score of 82.87. Furthermore, positive things were also found in the analyzed observation sheet data where students were always motivated, enthusiastic and did not feel bored in participating in the vocabulary learning process using the personal vocabulary note (PVN) method.